2014
DOI: 10.5541/ijot.480
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Analysis of a Gas Turbine Power Plant Modelled with an Evaporative Cooler

Abstract: In this paper the performance enhancement of gas turbine power plants by cooling the compressor intake air with an evaporative cooler is studied. This study investigated the effect of inlet air cooling system on the performance of an existing gas turbine power plant in Nigeria. The results show that for each 5 o C decrease of inlet air temperature, net output power increases around 5-10% and the thermal efficiency increases around 2-5%. It is shown that the amount of this increase is higher when the pressure r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 12 publications
(13 reference statements)
1
13
0
Order By: Relevance
“…Moreover, turbine inlet temperature is also limited by metallurgical property used by the manufacturer, hence, the maximum requirement temperature for this system was limited to1514 [K] as shown in Table I. The results obtained correspond to the result of Anoor and S. Oyedepo in reference [13] and [14]. Evaporative cooling of gas turbine decreases the compression work of the compressor and increases the efficiency of the system,that means compressor effectivenss is also another factor to be consider on simulations Fig.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Moreover, turbine inlet temperature is also limited by metallurgical property used by the manufacturer, hence, the maximum requirement temperature for this system was limited to1514 [K] as shown in Table I. The results obtained correspond to the result of Anoor and S. Oyedepo in reference [13] and [14]. Evaporative cooling of gas turbine decreases the compression work of the compressor and increases the efficiency of the system,that means compressor effectivenss is also another factor to be consider on simulations Fig.…”
Section: Resultssupporting
confidence: 59%
“…The mass flow rate of the fuel, specific fuel consumption and air fuel ratio are computed in equation (13) to (14), the mass of air entering turbine is 40 % of the air leaving compressor.…”
Section: Thermodynamic Equationsmentioning
confidence: 99%
“…Oyedepo and Kilanko [5] carried out a study on the thermodynamic analysis of a gas turbine power plant fitted with an evaporative cooler based in Nigeria. They concluded that power output increased by 5-10% and thermal efficiency by around 2-5% on decreasing the inlet air temperature by 5°C.…”
Section: Introductionmentioning
confidence: 99%
“…Gas turbines are ideal for this application as they can be started and stopped quickly, enabling them to be brought into service as required to meet energy demand peaks (Jaber et al, 2007). However, due to availability of natural gas at relatively cheap prices compared to distillate fuels, many countries around the world, e.g Nigeria, use large conventional GTs as base load units (Oyedepo and Kilanko, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Power rating can drop by as much as 20 to 30%, with respect to International Standard Organization (ISO) design conditions, when ambient temperature reaches 35 to 45°C (Mahmoudi et al, 2009;Guinee, 2001). One way of restoring operating conditions is to add an air cooler at the compressor inlet (Sadrameli and Goswami, 2007; (Oyedepo and Kilanko, 2014). The air cooling system serves to raise the gas turbine performance to peak power levels during the warmer months when the high atmospheric temperature causes the turbine to work at off-design conditions with reduced power output (Kakaras et al, 2004;Kamal and Zubair, 2006;Khaliq et al, 2009).…”
Section: Introductionmentioning
confidence: 99%